Tanggung Jawab Hukum PT. ID Express Logistik Indonesia Terhadap Kerusakan Barang dalam Pengiriman - Hasibuan, Dinny Orlanda Tidari; Yatini (International Journal of Politic, Public Policy and Environmental Issues, 2024)
This research examines the legal responsibility of PT. ID Express Logistik Indonesia for damaged goods during the delivery process, focusing on the application of Law Number 8 of 1999 concerning Consumer Protection. The methodology employed is normative legal research with a legislative and case study approach. The findings indicate that although consumers have the right to file compensation claims, the claim process is often hindered by reporting deadlines, verification procedures, and compensation limits set by the company. The case of consumer IS, who experienced damage to goods due to improper packaging, highlights an imbalance in legal protection for consumers. PT. ID Express frequently limits its liability through standard clauses in shipping agreements, which can create legal uncertainty. This study emphasizes the importance of balancing the rights and obligations between consumers and companies to establish legal certainty in goods delivery services. It is hoped that the results of this research can contribute positively to the development of consumer protection practices in Indonesia.